Neuropsychology of epilepsy in Malaysia: a narrative review - Normah Che Din, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study is to describe the development of neuropsychological research among epilepsy patients in Malaysia so far, the current trend and the focus of future research endeavour. The research in epilepsy grows concurrently with the interest in the field of neuropsychology in Malaysia. Beginning with the presurgical evaluation of epilepsy patients as part of the epilepsy protocols, research areas expanded further into neuropsychological profiling. The current trend in Malaysia is determining the factors influencing neuropsychological outcomes as well as the risk factors associated with low quality of life among epilepsy patients. The future neuropsychological research should emphasize on the effectiveness of neurorehabilitation of epilepsy patients as well as psychosocial and cultural issues particularly on social stigma and employability in line with the research priorities set by the Research Task Force of the ILAE Commission on Asian and Oceanian Affairs for people with epilepsy in Asia-Oceanic region.